Microcontroller for Temperature Condition Monitoring Systems on Transformers: Enabling Predictive Maintenance for Aviation - Amalia, Direstu; Ristumanda, Siti Salbiah; Sunardi, Sunardi; Martadinata, M. Indra (Universitas Dharma Wacana, 2025)
Airports heavily rely on stable electricity, with transformers as essential components for converting electrical voltage. High temperatures in transformers can cause degradation of the cooling oil, insulation damage, and a reduction in the transformer's lifespan that coul be degrade aviation safety standard. The incident on the transformer at SS2 Sultan Mahmud Badaruddin II Airport in Palembang due to overheating caused a significant impact on airport operations. This research aims to develop microcontroller technology to identify and predict potential issues in critical electrical components, particularly transformers, before failures occur and conduct the system testing. This effort is relevant to a safety strategy based on predictive maintenance to prevent accidents. This research using the fourth stage of the Maxim’s model of R&D method includes planning, development, and testing under conditions that resemble real-life situations. The research began by identifying needs through interviews and observations, which indicated the necessity of monitoring transformer temperature with early notifications and automatic exhaust fan control. The test results show that the system functions well in detecting temperature, activating the exhaust fan when the temperature reaches the threshold, and sending alarm notifications through the Blynk application. Suitability aspect testing indicate that the prototype received a positive response regarding functionality with an average score of 2.67, which falls into the valid feasibility category. It is expected to significantly contribute to developing microcontroller technology in safety, provide databased for predictive maintenance and offer practical solutions for improving the reliability and operational efficiency of electrical distribution systems at airports.